Research Papers of Acharya Prafulla Chandra Roy: A Bibliometric Study - Chakrabarti, Avijit; Chakrabarti, Biplab (Qualitative and Quantitative Methods in Libraries, 2017)
Abstract:  This study presents bibliometric analysis of the research papers of Acharya Prafulla Chandra Roy. He is one of the scientists who popularized science in India and truly known as the „Father of Indian Chemistry‟. During the period of 1888 to 1936, in a span of 49 years, he contributed 158 research papers in several reputed national and international journals. The analysis of his contributions includes year and periodical distribution of items, their language distribution, and single and multiple authorship. Year-wise distribution of pages authored by Acharya Prafulla Chandra Roy has also been presented as well as his journal preference based on periodical distribution of articles.